Los términos para el color blanco y su desarrollo semántico en la lengua asháninka - Solari Ruiz-Eldredge, Oscar Augusto (2020)
The main purpose of this research is to analyse kitamarori, kitamaari and kiteri; terms that belongs to white-color notion in Ashaninka language. These terms are the product of perception coding of different referents and tangible and intangible dimensions of nature manifested in various opaque components of its structure. Emphasis is placed on respective semantic development, for which we appeal to lexicalization theory and, for the belonging degree of each term in this category, to Basic Color Terms theory and prototype theory. The results show that kitamarori and kitamaari were built according to brightness and the aspect of its concretization manifested in the morning sky and in mythological beings, and kiteri, on the concept of cleanness related to the observation of the color of healthy skin of the Arawak people.